Identification and Risk Analysis of Mozarella Cheese Production Process - Farras Tsany; Imam Santoso; Dhita Morita Ikasari (Universitas Padjadjaran, 2017)
Mozzarella cheese is a food which is very risky to the growth of microorganisms since it has high water content by 54.1%. One way to overcome that problem is to identify and analyze the risks found in the production process of mozzarella cheese. Therefore, the researchers examined the identification and risk analysis of mozzarella cheese production process by conducting a case study in CV XYZ. The methods used were Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA). The results revealed that there were 11 risks from 8 steps of the production process. Of the 11 risks, the risks which were included in the critical risks were the risk of contamination during the curd clotting process, low-quality of milk, severe stretcher machine damage, and overly acidic cheese taste. The result of quantitative analysis of FTA indicated that the risk probability during mozzarella cheese production process was 0.110 or the risk was 11%. The probability with the highest value was the probability of contamination risk during the curd clotting process by 0.095. It indicated that contamination during the curd clotting process was the most probable risk in the future. The proposed recommendations for improvement are devising Standard Operating Procedures (SOPs) and Sanitation Standard Operating Procedures (SSOP) based on the company's condition and it should be implemented properly. Then, improving communication with suppliers is also needed so that the company will always get high quality raw materials. Keywords: Qualitative Analysis, Quantitative Analysis, Dairy Product, Failure Mode and Effect Analysis, Fault Tree Analysis